2009
DOI: 10.1016/j.carres.2008.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Modified citrus pectin anti-metastatic properties: one bullet, multiple targets

Abstract: In this minireview, we examine the ability of modified citrus pectin (MCP), a complex water soluble indigestible polysaccharide obtained from the peel and pulp of citrus fruits and modified by means of high pH and temperature treatment, to affect numerous rate-limiting steps in cancer metastasis. The anti-adhesive properties of MCP as well as its potential for increasing apoptotic responses of tumor cells to chemotherapy by inhibiting galectin-3 anti-apoptotic function are discussed in the light of a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
190
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(194 citation statements)
references
References 33 publications
2
190
0
2
Order By: Relevance
“…All human cells express carbohydrates on their surfaces in the form of glycoproteins, glycolipids and polysaccharides. Emerging studies indicate that plant pectin, a complex branched polysaccharide fiber rich in galactoside Science Publications AJPT residues, has been shown to play critical therapeutic roles against various cancers (Olano-Martin et al, 2003;Glinsky and Raz, 2009). Reports also suggest that pectic polysaccharides are involved in an immuno-modulation process (Wong et al, 1994) and possesses anti-ulcer effects (Kiyohara et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All human cells express carbohydrates on their surfaces in the form of glycoproteins, glycolipids and polysaccharides. Emerging studies indicate that plant pectin, a complex branched polysaccharide fiber rich in galactoside Science Publications AJPT residues, has been shown to play critical therapeutic roles against various cancers (Olano-Martin et al, 2003;Glinsky and Raz, 2009). Reports also suggest that pectic polysaccharides are involved in an immuno-modulation process (Wong et al, 1994) and possesses anti-ulcer effects (Kiyohara et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, humans cells are unable to produce pectin degrading enzymes to degrade the pectin; therefore, scientists have developed Modified forms of Citrus Pectin (MCP) (Baldwin and Shah, 1993;Pienta et al, 1995). Several recent independent studies have shown that MCP plays an important role in carcinogen detoxification and cancer suppression by its interaction with different oncogenes in cancer cells (Glinsky and Raz, 2009). MCP has been shown to play a more potential therapeutic role against various cancers compared to normal citrus pectin (Hayashi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from being utilised as specific drug carrier to the colon, pectin also has been studied for its antitumor activity. According to Glinsky and Raz [18], antitumor activity of pectin was attributed to abundant -galactose present in modified citrus pectin (MCP). The primary mechanism of action for MCP is by inhibiting a -galactoside binding protein galectin-3 (Gal-3), which is responsible for angiogenic activity.…”
Section: Cell Growth Inhibition Effect and Vegf Downregulationmentioning
confidence: 99%
“…This property enables it to be used as a specific drug carrier to the colon [17]. Besides, it also displays antitumor activity [18] that can further enhance growth inhibition or cytotoxic effect in colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%